Association of human TLR1 and TLR6 deficiency with altered immune responses to BCG vaccination in South African infants. - April Kaur Randhawa; Muki S Shey; Alana Keyser; Blas Peixoto; Richard D Wells; Marwou de Kock; Lesedi Lerumo; Jane Hughes; Gregory Hussey; Anthony Hawkridge; Gilla Kaplan; Willem A Hanekom; et al. (PLoS Pathogens, 2011)
The development of effective immunoprophylaxis against tuberculosis (TB) remains a global priority, but is hampered by a partially protective Bacillus Calmette-Guérin (BCG) vaccine and an incomplete understanding of the mechanisms of immunity to Mycobacterium tuberculosis. Although host genetic factors may be a primary reason for BCG's variable and inadequate efficacy, this possibility has not been intensively examined. We hypothesized that Toll-like receptor (TLR) variation is associated with altered in vivo immune responses to BCG. We examined whether functionally defined TLR pathway polymorphisms were associated with T cell cytokine responses in whole blood stimulated ex vivo with BCG 10 weeks after newborn BCG vaccination of South African infants. In the primary analysis, polymorphism TLR6_C745T (P249S) was associated with increased BCG-induced IFN-γ in both discovery (n = 240) and validation (n = 240) cohorts. In secondary analyses of the combined cohort, TLR1_T1805G (I602S) and TLR6_G1083C (synonymous) were associated with increased IFN-γ, TLR6_G1083C and TLR6_C745T were associated with increased IL-2, and TLR1_A1188T was associated with increased IFN-γ and IL-2. For each of these polymorphisms, the hypo-responsive allele, as defined by innate immunity signaling assays, was associated with increased production of TH1-type T cell cytokines (IFN-γ or IL-2). After stimulation with TLR1/6 lipopeptide ligands, PBMCs from TLR1/6-deficient individuals (stratified by TLR1_T1805G and TLR6_C745T hyporesponsive genotypes) secreted lower amounts of IL-6 and IL-10 compared to those with responsive TLR1/6 genotypes. In contrast, no IL-12p70 was secreted by PBMCs or monocytes. These data support a mechanism where TLR1/6 polymorphisms modulate TH1 T-cell polarization through genetic regulation of monocyte IL-10 secretion in the absence of IL-12. These studies provide evidence that functionally defined innate immune gene variants are associated with the development of adaptive immune responses after in vivo vaccination against a bacterial pathogen in humans. These findings could potentially guide novel adjuvant vaccine strategies as well as have implications for IFN-γ-based diagnostic testing for TB.